1982: Papers from the Conference: Communication at University: Purpose, Process and Product - Bock (Editor), Hanne; Gassin (Editor), June (Journal of Academic Language and Learning, 2026)
Formatting note: In the pdf, an article can be accessed directly by clicking on its title in the table of contents or via the Bookmarks pane. Foreword … I Part I Factors Influencing Effective Communication: Elizabeth Dines … 1 Assisting Student Learning – Some Recent Developments in Universities in the U.S. and U.K.: John Clanchy … 17 The Integration of Student Study Skills Sessions in a First-Year University Programme: Ortrun Zuber-Skerritt … 27 Marshalling Information – Concepts and Skills for Undergraduate Students: Ursula Newell … 50 Reversing an Effect of the TV Set – Computer Games as an Aid in Developing Literacy: Peter A. Caldwell and Rosalind Meyer … 57 A Formula for Writing? Rosalind Meyer … 62 Overcoming Legal Culture Shock: Gwen Morris … 78 Part II Modes of Communication and Culture: Michael Clyne … 101 Language is not Enough – Responses to the Academic Difficulties of Overseas Students: Brigid Ballard … 116 Role-Play as a Means to bridge Cultural Differences in Effective Communication: Gloria Chan … 129 Attitudes towards English – A Survey of Malaysian Chinese and Japanese Overseas Students at La Trobe University: June Gassin and Takeo Ida … 133 University Essays as Cultural Battlegrounds – The Problems of Migrant Students: Hanne Bock … 140